Analisis SWOT Terhadap Efisiensi Sistem Pelaporan Kegiatan Di Sekretariat Kecamatan Aranio Kabupaten Banjar - Syarani, Ridwan (GAYAKU PUBLISHER, 2023)
The obligations that must be fulfilled by the sub-district secretariat are related to the functions of planning, finance, assets and personnel, namely regularly reporting various activity reports required by stakeholder work units within a certain time period. Based on the results of the SWOT analysis, it can be concluded that the strategic analysis strategy for the efficiency of reporting in Aranio District is included in Quadrant I, because it has opportunities and strengths so that it can take advantage of existing opportunities. The strategy that must be implemented in this condition is to support an aggressive growth policy (growth), leading to a strategy of expansion/development, growth and expansion in certain fields, using strengths to take advantage of opportunities